Pengaruh Beban Kerja, Lingkungan Kerja, Kompensasi Karyawan terhadap Kepuasan Kerja pada PT. Rapigra Flexible Packaging pada Bagian Produksi - Hasna Huriyah; Sri Wahyuningsih (Departement of Mathematics Education, 2023)
This study aims to determine whether there is Workload (X1), Work Environment (X2), Employee Compensation (X3), Against Job Satisfaction (Y) in the Production Department of PT. Rapigra Flexible Packaging. The type of research used is quantitative. The research approach used in this research is analysis in research used in this research is descriptive analysis using questionnaire data on 80 respondents from a total population of 80 employees of the production division of PT. Rapigra Flexible Packaging. The sampling technique used is nonprobability sampling with saturated sample method. Test results t test (significant correlation) using the LISREL application version 8.80.